BRAF V600E mutations are frequent in dysembryoplastic neuroepithelial tumors and subependymal giant cell astrocytomas. Issue 3 (24th October 2014) - Lee, Dakeun; Cho, Young Hye; Kang, So Young; Yoon, Nara; Sung, Chang Ohk; Suh, Yeon‐Lim
<x xml:space="preserve">Abstract</x> Background BRAF mutation has received a great deal of attention in neuro‐oncology field, recently. This study aimed to investigate the incidence and the clinical significance of BRAFV600E in low‐grade glial tumors. Methods An institutional cohort of 105 brain tumors (51 dysembryoplastic neuroepithelial tumors (DNTs), 14 subependymal giant cell astrocytomas (SEGAs), 12 glioblastoma with neuronal marker expression (GBM‐N), and 28 pleomorphic xanthoastrocytomas (PXAs)) from 100 patients were investigated for the presence of BRAFV600E by direct sequencing. Results We found frequent BRAFV600E in DNTs (26/51, 51%), SEGAs (6/14, 42.9%), and PXAs (14/28, 50%). In DNTs, BRAFV600E was more commonly detected in tumors with extra‐temporal location (68.2% vs. 37.9%; P = 0.032). The diagnostic subgroups of tuberous sclerosis complex were not correlated with BRAFV600E in patients with SEGA (P = 0.533). One PXA case revealed a unique duplication mutation (p.Thr599dup) of codon 599. All GMB‐N cases did not carry BRAF mutation. Conclusions Our data indicate that BRAFV600E is a common genetic alteration in low‐grade glial tumors with neuronal component or differentiation. High frequency of BRAFV600E in DNTs and SEGAs would be useful in the differential diagnosis, and also offers a potential specific treatment targeting BRAFV600E. J. Surg. Oncol. 2015 111:359–364. © 2014 Wiley Periodicals, Inc.